Islamic Thought Movements in Egypt: Traditionalism - Modernism - Kacar Br Ginting; Nur Fadillah; Putri Rahmadini Hsb; Hafifah Hanim; Siti Khadijah (Al Yazidiy Jurnal Sosial Humaniora dan Pendidikan, 2026)
Egypt has been one of the most important centers for the development of Islamic intellectual movements in the Arab world, particularly from the 19th to the early 20th century. During this period, two major currents emerged that significantly shaped the intellectual dynamics of the Muslim community: traditionalism and modernism. Traditionalism sought to preserve the authority of classical scholarly heritage, the interpretive methods of earlier scholars, and religious educational systems rooted in long-established Islamic institutions. In contrast, modernism arose as a reformist movement advocating for the reinterpretation of Islamic teachings in order to align them with contemporary developments, scientific progress, and socio-political change.The debate between these two currents not only reflects differing approaches to understanding religious texts but also illustrates the broader effort of Muslims to respond to the challenges of modernity and colonialism. This article aims to analyze the development of Islamic intellectual movements in Egypt by highlighting the background of their emergence, their key characteristics, and the influence of both traditionalism and modernism in shaping Islamic intellectual discourse. This study employs a library research method by examining various sources related to the history and thought of Islam in Egypt. The findings indicate that the interaction between these two currents has produced a dynamic intellectual landscape that has significantly influenced the trajectory of Islamic reform in the Muslim world. However, this study is limited by its reliance on a library research method and secondary sources, which may not fully capture contemporary empirical dynamics of Islamic intellectual movements in Egypt; therefore, future studies are recommended to employ field research, interviews, or comparative analyses with other Muslim countries to obtain more comprehensive findings.